2019
DOI: 10.7717/peerj.7727
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNAs associated with lung squamous cell carcinoma prognosis in the competitive endogenous RNA network

Abstract: Background Long noncoding RNAs (lncRNAs) play a role in the formation, development, and prognosis of various cancers. Our study aimed to identify prognostic-related lncRNAs in lung squamous cell carcinoma (LUSC), which may provide new perspectives for individualized treatment of patients. Materials and Methods The RNA sequencing (lncRNA, microRNA (miRNA), mRNA) data and clinical information related to LUSC were obtained from The Cancer Genome Atlas (TCGA) database. Differentially expressed RNA sequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Our findings that lncRNAs can accurately discriminate BrCa from health indirectly support their contribution to tumor biology. The lncRNA AC078802.1 is an antisense to ACTRT3 and its aberrant expression has only been demonstrated in squamous lung cancer, presenting contradictory results so far [ 34 , 35 ]. Our methylome bioinformatics analysis revealed that AC078802.1 is hypermethylated in BrCa, opening the field for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that lncRNAs can accurately discriminate BrCa from health indirectly support their contribution to tumor biology. The lncRNA AC078802.1 is an antisense to ACTRT3 and its aberrant expression has only been demonstrated in squamous lung cancer, presenting contradictory results so far [ 34 , 35 ]. Our methylome bioinformatics analysis revealed that AC078802.1 is hypermethylated in BrCa, opening the field for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2019) demonstrated that lncRNA ERVH48-1 may be act as a latent signature of prognosis and treatment for tongue squamous cell carcinoma patients. Qi et al (2019) confirmed ERVH48-1 as a latent prognostic element for lung squamous cell carcinoma patients based on the ceRNA network analysis. Our study is the first report of the key role of ERVH48-1 in ceRNA networks, and its dysregulation is crucial for the development of BRCA aged ≥ 65 years.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, they showed that overexpression of LINC00261 reduced β-catenin and TCF4 expression and simultaneously increased E-cadherin, which is a TCF4 downstream target. In addition, other studies suggested that LINC00261 might act as a sponge for several miRNAs, as it was found in several comprehensive analyses of ceRNA networks in different types of cancer [73][74][75]. However, stringent experimental evidence that would clearly support a ceRNA function of LINC00261 is still lacking.…”
Section: Discussionmentioning
confidence: 97%